The Role of Postsecondary Institutional Urbanicity in College Persistence - P. Johnelle Sparks; Anne-Marie Nunez (Journal of Research in Rural Education, 2014)
Students from rural areas are less likely than their urban or suburban counterparts to attend college (Adelman, 2002; Hu, 2003). Although theorists have postulated that institutional urbanicity directly affects college student outcomes (Berger & Milem, 2000), few, if any empirical studies have examined the relationship between an institution's urbanicity and the outcome of individual student persistence. This study employs multilevel modeling to examine the effect of attending a rural institution on individual student persistence. We fi nd persistence does not differ by residential location; however, student level characteristics vary greatly by the location of the four-year institution attended. Additionally, several of the institutional level characteristics, including other structural, peer, and fi nancial organizational factors, as well as local economic conditions, have an independent effect on individual student persistence. These characteristics vary signifi cantly depending on if the institution is located in a rural, suburban, or urban location.